Uji Aktivitas Ekstrak Etanol Daun Lidah Buaya (Aloe Vera) Terhadap Penghambatan Pertumbuhan Staphylococcus aureus Dan Candida albicans - Gemy Nastiti Handayani (INSTITUT AGAMA ISLAM NEGERI AMBON, 2019)
This study aims to determine the activity of ethanol extract of Aloe vera leaves against Staphylococcus aureus bacteria and Candida albicans fungi. Extraction of aloe vera leaves is done by maceration method, then extracted several concentrations, namely 2.5%, 3.5%, and 4.5% for Staphylococcus aureus bacteria and concentrations of 4%, 8% and 12% for Candida albicans fungi. The inhibitory testing is done by agar diffusion method. The test results showed that the ethanol extract of Aloe vera leaves had antibacterial activity of Staphylococcus aureus and anti-fungal Candida albicans which was characterized by the presence of a clear zone. In Staphylococcus aureus bacteria provide optimum inhibition zone at a concentration of 4.5% with a diameter of 10.8 mm while in, the fungus Candida albicans provides the optimum inhibition zone at a concentration of 12% with a diameter of resistance 18.87 mm. Key Words: Ethanol, Aloe vera leaves, Staphylococcus aureus, Candida albicans